Moraxella osloensis Bacteremia in an Immunocompetent Child - Purohit, Prashant; Sadek, Sherif Abdul Latif; Tak, Komal; Emara, Maha; Bafna, Ritu; Al-Obaid, Ina'am Ahmad; Habibi, Nazima; Mustafa, Abu Salim (Journal of Pediatric Infectious Diseases, 2020)
Moraxella osloensis has been reported in the literature as a rare cause of sepsis, central nervous system infection, chest infection, and endophthalmitis. In the present case, the organism was isolated from the blood of an 8-year-old immunocompetent boy. It could not be identified with VITEK-2 and API-20NE (bioMerieux SA, Marcy-l'Etoile, France). Latex-based bacterial antigen test (BD Directigen Meningitis Combo Test; Becton, Dickinson and Company, Sparks, Maryland, United States) was positive for Neisseria meningitidis A/Y. It was identified as M. osloensis using matrix-associated laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF) (Vitek MS, bioMerieux, Marcy-l'Etoile) (confidence level 99.9%) and 16S rRNA gene sequencing (99% sequence identity). The child responded well to ampicillin, and was discharged home after 4 days, on oral amoxicillin–clavulanic acid for the next 7 days. M. osloensis is a rare cause of bacteremia. It may masquerade as N. meningitidis in the routine tests performed in the routine microbiology laboratories. It is imperative to confirm the identification with MALDI-TOF or a molecular method to remove the false positive diagnosis of N. meningitidis, and to avoid the unnecessary use of prophylaxis with rifampicin or ciprofloxacin.
Keywords: gram-negative diplococci; blood stream infection; paranasal sinusitis